Đáp án:
Giải thích các bước giải:
$\text{a,(x+2)(x²-3x+4)-x(x+3)(x-3)=26}$
$\text{⇔x³+8-x(x²-9)=26}$
$\text{⇔x³+8-x³+8x-26=0}$
$\text{⇔8x-18=0}$
$\text{⇔2(x-9)=0}$
$\text{⇔x-9=0⇔x=9}$
$\text{Vậy x= 9}$
$\text{b, (x-3)(x²+3x+9)-x(x-4)(x+4)=21}$
$\text{⇔x³-27-x(x²-16)=21}$
$\text{⇔x³-27-x³+16x-21=0}$
$\text{⇔16x-48=0}$
$\text{⇔16(x-3)=0}$
$\text{⇔x-3=0⇔x=3}$
$\text{Vậy x=3}$
$\text{c, (2x-1)(4x²+2x+1)-4x(2x²-3)=23}$
$\text{⇔8x³-1-8x³+12x=23}$
$\text{⇔12x-1-23=0}$
$\text{⇔12x-24=0}$
$\text{⇔12(x-2)=0}$
$\text{⇔x-2=0⇔x=2}$
$\text{Vậy x=2}$